STRESS INDIVIDU, KONDISI KERJA DAN PRODUKTIVITAS KARYAWAN: (Studi Kasus di PT. Sarana Kreasindo) - Sir Kalifatullah Ermaya; Iwan Mulyana; Rosti Setiawati (Jurnal Co Management, 2019)
This research aims to describe individual stress, workplace condition and employee productivity in PT Sarana Kreasindo. This research was done because the researcher found that there were problems regarding those three variables. The total amount of respondents used in this research were 70 employees.Statistical tool used was SPSS. Statistical methods used were validity test, reliability test, classical assumption test, and impact test. The result showed that Individual Stress Variabel (X1) partially had an impact significantly on Productivity Variable (Y). Furthermore, Workplace Condition (X2) partially didn’t have any impacts and unsignificant on Productivity (Y). Finally, Individual Stress Variable (X1) and Workplace Condition (X2) simultaneously had positive impact but unsignificant on Productivity variable (Y).